Cassius Marcellus Clay : Firebrand of Freedom. - Richardson, H. Edward (Harold Edward), 1929-2008 (Kentucky Bicentennial bookshelf., 1976)
The most colorful member of Kentucky's most illustrious family, Cassius Marcellus Clay is a legendary figure in the Bluegrass. This lively biography records both the traditions surrounding Clay and the historical facts of his life, which are themselves the stuff of legend. Although Clay was a dedicated emancipationist, his real interest lay in broad issues of human freedom. The story of Clay's True American, his service in the Mexican War, his accomplishments as Lincoln's minister to Russia, and his active post-Civil War political life are all told against the background of the climactic even.